Parallel evolving morphology, magnetic properties and their relationships in Ni₀.₅Zn₀.₅Fe₂O4 - Ismail, Ismayadi (2012)
For more than seven past decades, the ferrite research literature has only very superficially dealt with the question of how the evolving microstructure of a ferrite material relates to its accompanying, resultant magnetic properties. The literature has only covered in great detail the answers for the case of ferrite materials obtained from final sintering. Thus, this work was a fresh attempt to critically track the evolution of magnetic properties parallel to the microstructural changes in bulk Ni0.5Zn0.5Fe2O4 samples and to relate the properties to the changes wherever possible. The study was divided into five parts. The first part involved two variables (milling time and ball to powder weight ratio (BPR)) of a mechanical alloying process where they were varied in order to study their effect on the magnetic properties of the material. The alloyed powders were used as starting powders for the rest of the research work. In the second part, parallel sintering of a number of samples was carried out with sintering temperatures of 500 to 1400oC, subjecting one sample to only one particular sintering temperature. This was a multi-sample sintering process with 100oC increments. The third part dealt with higher-precision multi-sample sintering of several samples with sintering temperatures of 800 to 1000oC with much smaller increments of 25oC. The fourth part involved studies of the effect of soaking time on microstructural evolution and its influence on the magnetic properties. The last part carried out was similar to the second part (multi-sample), but it was run more carefully and critically with only one sample (single-sample) being subjected to various ascending sintering temperatures from 500 to 1400oC. The results from first-part on the mechanical alloying parameters variation showed that there were no significant trends to relate the milling time and BPR with the permeability and losses of the material studied. After the samples were sintered at 1150oC, all the effects of the alloying process seemed to diminish. The results from the multi-sample sintering with the nanosized starting powders subjected to various sintering temperatures showed a clear development trend of the phase, morphology and magnetic properties of the samples. It is very interesting that the results revealed a critical region of sintering temperature for the development of magnetic properties which was observed at 800oC and 900oC with the sigmoid B-H curve shape taken to indicate a strong magnetic order. For the first time, this work has reported the evolution of the B-H hysteresis loops associated with the changes of magnetic states from paramagnetism to moderate ferromagnetism to strong ferromagnetism with microstructural changes. The results of the higher precision third part on the relationship between ordered magnetism and the microstructure of the samples revealed a very startlingly systematic trend: a highly refined evolution trend covering a critical region of ordered magnetism which emerged and developed in step with morphological changes. Further work on the soaking time parameter was to study another possible way for the microstructure to influence the magnetic properties. The results showed a slow grain growth rate indicating a slow diffusion of atoms during the sintering process: it is believed that there was an increase in number of grain growth spots and these were the regions of mixed superparamagnetic and paramagnetic mass with ferromagnetic mass starting to dominate the samples. The last part of this work, carried out using single-sample sintering, also produced very gratifying results from the research point of view: the fascinating results from the single-sample sintering showed very systematically the evolution of microstructure-magnetic property relationships with a clarity superior to that shown by the multi-sample sintering. Finally, after analysing the results and the observations of the work mentioned above, it is strongly believed that there are three factors found to sensitively influence the samples content of ordered magnetism –their ferrite-phase crystallinity degree, the number of grains above the critical grain size and large enough grains for domain wall accomodation. This research work has shed new light on the microstructure-magnetic properties evolution in ferrites.